Association between soluble α-klotho and mortality risk in middle-aged and older adults - Chuang, Min-Hsiang; Wang, Hung-Wei; Huang, Yun-Ting; Jiang, Ming-Yan (Frontiers in Endocrinology, 2023)
Studies on association of α-klotho levels with mortality risk in general population are relatively scarce and inconclusive. Therefore, we conducted a population-based cohort study using a nationally representative sample of middle-aged and older adults in the United States (U.S.) to investigate the relationship between soluble α-klotho and all-cause mortality. The study population was 2007-2016 National Health and Nutrition Examination Survey (NHANES) participants, totaling 13,583 adults aged 40-79 years. Participants were divided into 7 groups by septile of α-klotho levels. We linked the NHANES data to the National Death Index to determine participants' survival status. End of followup was participants' death date or December 31, 2019. We observed that males, current smokers, older age, higher body mass index, and lower estimated glomerular filtration rate correlated to lower α-klotho levels, while hepatitis C virus infection correlated to higher α-klotho. The population mortality rate was 11.8 per 10,000 person-months (1,490 deaths); group 1 (the first septile) had higher mortality risk compared with group 2 through group 7. By weighted Cox regression with adjustment for potential confounders, we found that group 2 through group 6, but not group 7, were associated with 25% to 35% lower risk of all-cause mortality compared with group 1. When compared with group 4, we observed that both group 1 (HR: 1.46, 95% CI 1.13-1.88) and group 7 (HR: 1.38, 95% CI 1.09-1.75) were associated with higher mortality risk. In summary, among middle-aged and older U.S. adults, we observed a non-linear association between soluble α-klotho and all-cause mortality, with individuals at the two extremes at increased risk of death.